Изучение реакции ненасыщенных оксазолонов с аминометилбензимидазолом - Мангасарян, С. Г.; Акопян, Э. А.; Шахатуни, А. А.; Топузян, В. О. («Գիտություն» հրատ.)
Իրականացվել է ամիդների, իմիդազոլոնների, եռցիկլերի սինթեզը, ուսումնասիրվել են առաջացած նյութերի ֆիզիկաքիմիական հատկանիշները և հակառադիկալային հատկությունները: Ստացված ամիդների, իմիդազոլոնների, եռցիկլերի հետևյալ տեղակալիչներով՝ C6H5, 4-CH3O-C6H4, 3,4-OCH2O-C6H3, 3-O2N-C6H4, 4-(4-CH3-C6H4 -SO2O)-C6H4, 3-CH3O-4-C6H5COO-C6H3, 3-CH3O-4-HO-C6H3 շարքում, 3-CH3O-4-HO-C6H3 տեղակալիչով իմիդազոլոնը ցուցաբերել է համեմատաբար բարձր հակառադիկալային ակտիվություն՝ ~34,1%, իսկ համապատասխան ամիդը՝ 70,2% ։ Ուսումնասիրվել են նաև սինթեզված նյութերի UV-սպեկտրները, հաշվարկվել են նրանց լուսակլանման մոլյար գործակիցները λmax- ի համար: The synthesiss of amides, 1, 2, 4- trisubstituted imidazole-5-ones, 3-oxobenzo[4,5]imidazopyrazines has been carried out. The physicochemical characteritics and antiradical properties of synthesizes compounds have been studied. In a series of amides, imidazolones and threecycles with substituents C6H5, 4-CH3O-C6H4, 3,4-OCH2O-C6H3, 3-O2N-C6H4, 4-(4-CH3-C6H4 -SO2O)-C6H4, 3-CH3O-4-C6H5COO-C6H3, 3-CH3O-4-HO-C6H3, the compound -imidazolone with substituent 3-CH3O-4-HO-C6H3 has shown a high antiradical activity equal to 34,1%, and its amids has to 70,2%. Also UV spectra of the synthesized substances have been studied. The molar light absorption coefficients εmax have been calculated at λmax.
Keywords: Органическая и биоорганическая химия